FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - IGNES JANUAR CAHYADI; MUHAMMAD HAASYIM ASYAM (E-Jurnal Akuntansi TSM, 2021)
The purpose of this research is to examine and found out empirical evidence about effects of factors like Managerial Ownership, Institutional Ownership, Concentrated Ownership, Liquidity, Firm Size, Profitability and Dividend Policy have to Firm Value. The data for this research consisted of 35 non-financial company listed in Indonesia Stock Exchange. The data was selected using purposive sampling method during the period 2014-2016. The data was analyzed using multiple linear regression method. The result of this study shows that Managerial Ownership, Institutional Ownership, Concentrated Ownership, Liquidity and Firm Size don’t affect the firm value. Another independent variables such as Profitability and dividend policy have influence toward firm value.